Advancements in Enhancing the Thermal Conductivity of Pristine Polyolefins - Chaudhry, A.U.; Rabbani, Harris; Mabrouk, Abdelnaser; Abdala, Ahmed (Science and Technology: Developments and Applications Vol. 9, 2025)
Because of their low cost, ease of processing, diverse functionality, excellent corrosion and chemical resistance, adequate tribological performance, superior thermal and environmental stability, and lightweight, polymers and their composites have received considerable attention over the last few decades. The low thermal conductivity of polymers hinders their use in applications requiring high thermal conductivity, such as electronic packaging, heat exchangers, and thermal management devices. Polyethylene and polypropylene (polyolefins) account for ~55% of the global thermoplastic production. Improving the thermal conductivity of this class of thermoplastics is essential for many applications. This comprehensive review analyzes the advances in enhancing the thermal conductivity of pristine polyolefins. First, the mechanism of thermal transport in polymers and the key parameters that govern conductive heat transfer through polymers are discussed. Moreover, the progress in modeling and simulation of the thermal conductivity of polyolefins is analyzed. Furthermore, the different approaches to enhance the thermal conductivity of polyolefins by controlling their microstructure, crystallinity, and chain orientation are presented. Finally, the key challenges and prospective directions for developing thermally enhanced pristine polyolefins are outlined. The study concluded that the application of machine learning can accelerate the development of thermally enhanced polyolefins.